A CASE OF REFRACTORY BRADYCARDIA SECONDARY TO BAROREFLEX FAILURE IN A PATIENT WITH SUPRASELLAR GERMINOMA - SS, Carolina; WH, Kang; M, Aina; K, Nur Azmi; S, Norlela (Journal of the ASEAN Federation of Endocrine Societies, 2019)
INTRODUCTION Germinoma in the fourth ventricle is an extremely rare occurrence and it has not been reported in association with baroreflex failure. CASE We report a 21-year-old man who presented with polyuria and polydipsia associated with gradual weight loss, headache and postural giddiness for 8 months. Physical examination revealed a blood pressure of 72/42 mmHg and a pulse rate of 42 beats per minute. Neurological examination revealed cranial nerves VI, IX and X palsies. His sodium was 150 mmol/L, serum osmolarity 333mosm/ kg and urine osmolarity 217 mosm/kg. MRI brain revealed a large suprasellar mass measuring 5.6 x5.6 x 5.0 cm extending into the sellar with enhanced lesions at the ependymal lining of the fourth ventricle. The diagnosis of panhypopituitarism with cranial diabetes insipidus was made. Intravenous hydrocortisone, oral desmopressin and levothyroxine were administered and a biopsy confirmed the suspicion of germinoma. Despite inotropic support, he remained bradycardic. Attempts to increase his heart rate and normalise his blood pressure with fludrocortisone, oral salt, temporary pacemaker and octreotide were futile. The inotropic support was finally withdrawn with the introduction of oral methylphenidate which is a central nervous system stimulant and peripheral vasoconstrictor. The patient subsequently underwent adjuvant chemotherapy and radiotherapy. Intact baroreflex function is required for appropriate cholinergic and adrenergic influence on heart rate and blood pressure. Input from the carotid sinus is delivered to the nucleus tractus solitarii located near the fourth ventricle via the glossopharyngeal nerve which then sends signals to the heart and blood vessels via sympathetic and parasympathetic nerve fibres. CONCLUSION Baroreflex failure should be suspected in patients with suprasellar or sellar tumours with fourth ventricle involvement who present with severe bradycardia and hypotension despite being adequately replaced with hydrocortisone and thyroxine. The use of methylphenidate should be considered when there’s failure of other treatment options.